1972
DOI: 10.1063/1.3253105
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Calibration: A Critical Review

Abstract: A critical review of experimental technique for measuring high pressures has been made. The broad coverage includes discussions relating to (a) the establishment of a primary pressure scale using the free-piston gage, (b) the selection and precise measurement of identifiable phase changes as fixed pressure points, and (c) the use of interpolation and extrapolation techniques such as resistance gages, equations of state, and optical changes. The emphasis is on static pressure measurements above 10 kbar, but sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

1978
1978
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(65 citation statements)
references
References 51 publications
0
63
0
2
Order By: Relevance
“…The room-temperature pressure calibration was carried out by monitoring the resistance changes in Bi [50] and Ba [51]. The pressure calibration at high temperature was performed using known phase transitions in SiO 2 (quartz-coesite) [52] and CaGeO 3 [53] at 1100°C.…”
Section: Methodsmentioning
confidence: 99%
“…The room-temperature pressure calibration was carried out by monitoring the resistance changes in Bi [50] and Ba [51]. The pressure calibration at high temperature was performed using known phase transitions in SiO 2 (quartz-coesite) [52] and CaGeO 3 [53] at 1100°C.…”
Section: Methodsmentioning
confidence: 99%
“…The equation of state of NaCl has been repeatedly investigated by previous studies [e.g. 21,[24][25][26][27][28][29][30][31]. In the future, a reliable equation of state for NaCl will be proposed, and the phase boundary between the semiconducting and the metallic phase determined in our study should be revised using the reliable equation of state.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that the calibrant is of high crystal symmetry, introducing only a few well-defined parasitic peaks to the diffraction pattern. A useful critical review of these methods may be found in the work of Decker et al [69] and Klotz [16].…”
Section: Methods Of Pressure Measurementmentioning
confidence: 99%